Homogeneous Core/Shell NiMoO4@NiMoO4 and Activated Carbon for High Performance Asymmetric Supercapacitor - Jia Yi Dong; Jin Cheng Xu; Kwun Nam Hui; Ye Yang; Shi Chen Su; Lin Li; Xi Tian Zhang; Kar Wei Ng; Shuang Peng Wang; Zi Kang Tang (Nanomaterials, 2019)
Here, we report the extraordinary electrochemical energy storage capability of NiMoO4@NiMoO4 homogeneous hierarchical nanosheet-on-nanowire arrays (SOWAs), synthesized on nickel substrate by a two-stage hydrothermal process. Comparatively speaking, the SOWAs electrode displays superior electrochemical performances over the pure NiMoO4 nanowire arrays. Such improvements can be ascribed to the characteristic homogeneous hierarchical structure, which not only effectively increases the active surface areas for fast charge transfer, but also reduces the electrode resistance significantly by eliminating the potential barrier at the nanowire/nanosheet junction, an issue usually seen in other reported heterogeneous architectures. We further evaluate the performances of the SOWAs by constructing an asymmetric hybrid supercapacitor (ASC) with the SOWAs and activated carbon (AC). The optimized ASC shows excellent electrochemical performances with 47.2 Wh/kg in energy density of 1.38 kW/kg at 0−1.2 V. Moreover, the specific capacity retention can be as high as 91.4% after 4000 cycles, illustrating the remarkable cycling stability of the NiMoO4@NiMoO4//AC ASC device. Our results show that this unique NiMoO4@NiMoO4 SOWA has great prospects for future energy storage applications.